Monitoring student performance using computer technology - Романенко, В’ячеслав; Тропін, Юрій; Бойченко, Наталя; Голоха, Валерій (Slobozhanskyi Herald of Science and Sport, 2019)
Vyacheslav Romanenko, Yura Tropin, Natalya Boychenko & Valeriy Goloha Purpose: to develop a computer program for students of the department of martial arts of KSAPC, which allows you to monitor and account for their knowledge in the discipline "Theory and methods of the chosen sport" and "Varieties of wrestling". Material & Methods: analysis of scientific and methodological information, computer programming method. Results: analysis of scientific and methodological information confirmed the relevance and significance of the problem of using computer technologies that create conditions where the student becomes an active subject of educational activity interested in achieving the goals of vocational education. The use of computer test programs is a fairly perfect means of monitoring and evaluating knowledge because of its objectivity in analyzing the results obtained. A computer program, CCT (ControlComplexTasks), designed for use in mobile devices, which allows you to quickly evaluate the current and course performance of students of the department of martial arts, was developed. Based on the analysis of teaching materials on the discipline "Theory and methodology of the chosen sport" (specialization "Wrestling", "Judo and Sambo", "Martial Arts") and the general course "Varieties of Wrestling" 520 control and integrated tasks for 1–4 year students of the department of martial arts, consisting of questions and three answers, one of which is correct. Conclusions: a computer program has been developed and introduced into the educational process, which allows monitoring and accounting for the mastering of theoretical knowledge of students of the martial arts department of the KSFC in the discipline "Theory and methodology of the chosen sport" and "Varieties of wrestling".